"On Water", Phosphine‐Free Palladium‐Catalyzed Room Temperature CH Arylation of Indoles. Issue 45 (7th October 2013) - Islam, Saidul; Larrosa, Igor
<x xml:space="preserve">Abstract</x> Get on top of your chemistry! An "on water", palladium‐catalyzed, phosphine‐free direct CH arylation of indoles, with iodoarenes at 25–30 °C, is disclosed (see scheme; TBDMS=N‐tert‐butyldimethylsilyl ether; SEM=N‐2‐(trimethylsilyl)ethoxymethyl; Bn=benzyl, Piv=pivabyl). The mildness of the reaction conditions permits the tolerance of a variety of N1‐protected indoles.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>